Coordinated sensing coverage optimisation in sensor networks using RSSI. (25th March 2021) - Huang, Qingdong; Zhou, Yun; Hao, Sen; Yao, Xueqian; Zhang, Miao
We present a coordinated algorithm for sensors' effective deployment, which aims to optimise coverage and surveillance in distributed sensor networks. In this paper, the easy accessed received signal strength indication (RSSI) is adopted to form virtual force, the virtual force algorithm for coverage optimisation will encounter oscillation problems when it has nearly reached an optimised position. We propose a new method which combines virtual force algorithm and the whale swarm algorithm (WSA) according to the RSSI value. When the number of continuous oscillations using a virtual force algorithm is greater than the threshold we set in advance, we optimise the cooperative position of adjacent multi-nodes with the whale swarm algorithm. The regular signal transmission model and radio irregularity model (RIM) are used to simulate the ideal environment and the actual environment, and simulation results demonstrate that the coverage ratio is above 95%, which verifies the effectiveness and feasibility of this algorithm.